The Cognitive and Affective Components of Organisational Identification: The Role of Perceived Support Values and Charismatic Leadership. Issue 4 (20th November 2012) - Xenikou, Athena
<x xml:space="preserve">Abstract</x> This study set out to investigate how the strength of organisational identification is related to organisational support values and charismatic leadership. The perception of organisational support values by an individual employee is a contextual factor which determines whether (a) organisational attributes similar to the self‐concept become salient leading to cognitive identification, and (b) an affective tie between the individual employee and the work organisation is developed. Charismatic leadership, on the other hand, builds a group identity among followers primarily by emotion‐arousing leadership behavior, and therefore was hypothesised to relate more strongly to affective, rather than cognitive, identification. Two hundred employees from a public organisation filled in a number of questionnaire measures of organisational support values, charismatic leadership, and organisational identification. The findings showed that support values predicted both cognitive and affective identification, whereas charismatic leadership was a predictor of affective identification. There was also a significant interaction effect of organisational support values and charismatic leadership on affective identification; in the condition of low support value orientation, charismatic leadership was shown to be positively associated with affective identification. These findings indicate that organisational values are basic elements of self‐implicating processes in organisational contexts, and their practical implications are discussed.